1998
DOI: 10.1038/sj.leu.2401097
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus and Hodgkin’s disease: further evidence for the three disease hypothesis

Abstract: The epidemiology of Hodgkin's disease suggests that it is a heterogeneous condition comprising more than one disease entity. The Epstein-Barr virus (EBV) is present in the ReedSternberg cells of a proportion of cases and is likely to play a role in the pathogenesis of these cases. In this study we show that EBV association rates vary with age at diagnosis. We suggest that Hodgkin's disease can be divided into three disease entities on the basis of EBV association and age, thereby providing biological support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
4
4

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 38 publications
4
106
4
4
Order By: Relevance
“…The EBV-positive rate in comparable cases of HD by age in the series of Armstrong et al 18 and this series is given in Table 3. Our series failed to show that the frequency of EBV-associated HD was greatest in age groups 0-14 years and 45+ years, compared with 15-34 years and 35-44 years.…”
Section: Ebv-positive Rate By Age: a Comparison Of Case Seriesmentioning
confidence: 84%
See 2 more Smart Citations
“…The EBV-positive rate in comparable cases of HD by age in the series of Armstrong et al 18 and this series is given in Table 3. Our series failed to show that the frequency of EBV-associated HD was greatest in age groups 0-14 years and 45+ years, compared with 15-34 years and 35-44 years.…”
Section: Ebv-positive Rate By Age: a Comparison Of Case Seriesmentioning
confidence: 84%
“…[7][8][9] Evidence of an association at the cellular level was provided by the localisation of EBV DNA 10,11 and the latent gene products, including the EBERs, 12 the Epstein-Barr nuclear antigen-1, 13 and the latent membrane proteins-1 14,15 and -2, 16,17 to the malignant Hodgkin and Reed-Sternberg (HRS) cells of HD. The frequency of EBV-associated HD has been shown to vary with age, [18][19][20] sex, 21 histological subtype, 19 country of residence 21 and ethnicity. 21 In a recent study from the UK, the frequency of EBV-associated HD was found to be higher in the age groups 0-14 years and 45+ years when compared to patients in the 15-34 or the 35-44 age groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For EBV-positive HL, this inconsistency may result from our limited statistical power due to the low prevalence of this form of HL in women. However, for EBV-negative HL, the null findings are somewhat unexpected, 23 given the prior evidence for infection-related risk factors in HL overall, 4,24-29 which primarily comprises EBV-negative disease in this and most adult populations.…”
Section: Discussionmentioning
confidence: 85%
“…[3][4][5] Later studies using methods to detect gene products of EBV within tumor cells, considered evidence of etiologic involvement, led to an unexpected conundrum: EBV is not detected in tumors of most young adults with HD. 6,7 This apparent paradox renewed interest in the possibility that elevated anti-EBV antibody titers in young-adult HD patients are markers for another etiologic virus. 5 As reported recently in this journal, Gallagher et al 8 have searched for herpesviruses in HD tumors, using 2 PCR assays shown to detect all known viruses in this family.…”
Section: Dear Sirmentioning
confidence: 99%